Transdifferentiation-dependent expression of α-SMA in hepatic stellate cells does not involve TGF-β pathways leading to coinduction of collagen type I and thrombospondin-2 - Lindert, Susanne; Wickert, Lucia; Sawitza, Iris; Wiercinska, Eliza; Gressner, Axel M.; Dooley, Steven; Breitkopf-Heinlein, Katja (Matrix biology, 2005)
Hepatic stellate cells (HSC) cultured on plastic spontaneously transdifferentiate to a myofibroblast-like cell type (MFB). This model system of hepatic fibrogenesis is characterized by phenotypic changes of the cells and increased matrix synthesis. Here, we analyzed if transdifferentiation-dependent induction of ECM components, e.g., collagen type I and thrombospondin-2 (TSP-2), and phenotypic changes are coregulated events and if both processes are mediated via TGF-β pathway(s). Blocking the TGF-β-dependent p38 MAPK pathway in HSC with the specific inhibitor SB203580 strongly reduces collagen I and TSP-2 mRNA expression without inhibiting upregulation of the typical MFB-marker, α-smooth-muscle actin (α-SMA). Similarly, interference with the Smad2/3/4 pathway using dexamethasone also heavily decreased expression of collagen type I and TSP-2 whereas transdifferentiation of HSC to the typical morphology of MFB with loss of fat droplets and increasing α-SMA was unchanged. Further, p38 MAPK mediated induction of collagen I and TSP-2 expression by TGF-β1 was still achieved in the presence of dexamethasone, showing that dexamethasone does not block p38 while it delays Smad2 phosphorylation and antagonizes stimulation of a Smad3/Smad4 dependent TGF-β reporter construct. Interestingly, in contrast to SB203580 and dexamethasone, overexpression of the TGF-β antagonist Smad7 reduced ECM expression and simultaneously inhibited morphologic transdifferentiation, indicating that Smad7 fulfills additional features in HSC. In conclusion, our data show that phenotypic changes of transdifferentiating HSC and induction of matrix synthesis are independent processes, the latter being stimulated by both, Smad dependent and MAPK dependent TGF-β signaling.
Gesehen am 23.06.2022